2011
DOI: 10.1177/1040638711425952
|View full text |Cite
|
Sign up to set email alerts
|

Localization of Bovine papillomavirus in equine sarcoids and inflammatory skin conditions of horses using laser microdissection and two forms of DNA amplification

Abstract: Abstract. Equine sarcoids are the most common tumor of horses. Bovine papillomavirus (BPV) has been suggested as the cause of sarcoids. Studies have shown that BPV is present in swabs or biopsies from nonsarcoid-bearing equine skin. Skin biopsies from a variety of different conditions and normal skin from horses with no reported history of sarcoids were examined by polymerase chain reaction (PCR) for the presence of BPV, which was found in all different types of skin conditions as well as normal skin. Forty-on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
1
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 26 publications
2
36
1
2
Order By: Relevance
“…1,19 Further work is necessary to understand how and when these events of the viral life cycle occur and their relationship to sarcoid development and/or maintenance. We propose, as have others, 8,37 that early in sarcoid development, there could be an early viral infection in the adnexa or surface epithelium that is undetectable later in the development of the tumor.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…1,19 Further work is necessary to understand how and when these events of the viral life cycle occur and their relationship to sarcoid development and/or maintenance. We propose, as have others, 8,37 that early in sarcoid development, there could be an early viral infection in the adnexa or surface epithelium that is undetectable later in the development of the tumor.…”
Section: Discussionmentioning
confidence: 99%
“…In these studies, BPV DNA was detected not only at high frequencies in the dermal tissue (fibroblasts), as we saw with ISH, but also, less prominently, in the epidermis. 8,11,37 Similarly, we specifically visualized BPV DNA in the sebocytes, hair follicle epithelium, and rarely epidermal cells. Detection in sebocytes has also been reported in related viruses, including Bandicoot papillomatosis carcinomatosis virus type 1, 7 human papillomaviruses, 16 and Micromys minutus papillomavirus.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in contrast to E2-TA, E2-TR activated transcription from a promoter-proximal position and partially inhibited P89, while E8E2 led to complete repression. In a recent study, viral DNA has also been found in the epidermis of horses with inflammatory skin conditions and in the epidermis overlying sarcoids, especially in early-stage, "occult", flat lesions [53]. Results suggest that a transient, productive infection may take place in the overlying epidermis during the early phases of sarcoid development [54][55].…”
Section: Bpv Persistence Latency and Transmissionmentioning
confidence: 92%